Postharvest quality of 'Camila' and 'Laetitia' plums harvested at different maturity stages Qualidade pós-colheita de ameixas 'camila' e 'laetitia' colhidas em diferentes estádios de maturação - Stanger M.C.* (2014)
This work was carried out to investigate the effect maturity stage at harvest (M1, M2 and M3, corresponding to fruit with 20-25%, 45-50% and 70-75% of peel red color surface, respectively) of 'Camila' and 'Laetitia' plums, and then stored in conventional cold storage, on ripening and quality, especially regarding the incidence of flesh browning. Fruits were cold stored during 40 days (1±0.1 °C and 95±2% RH), followed by three days at ambient condition (23±5 °C and 60±5% RH). 'Camila' plums harvested at maturity stage M1 showed the poorest evolution of peel red color during cold storage. Only fruit harvested at stage M3 had a good flesh red color development. The values of flesh firmness and force for fruit compression were different between maturity stages, being higher in M1 than in M2 and M3. On the other hand, fruit harvested at stage M1 had the highest force for flesh penetration. However, 'Camila' plums harvested with up to 50% of peel red color did not ripe satisfactory and had poor quality. 'Laetitia' plums showed satisfactory evolution of peel red color during cold storage, especially when harvested at stage M3. For this cultivar, the force for fruit compression was different between maturity stages, in the following order: M1>M2>M3. Titratable acidity was highest in fruit harvested at stage M1, while ethylene production rate was highest for fruit harvested at stage M3. 'Laetitia' plums harvested at the three maturity stages had similar ripening during cold storage. However, fruits should not be harvested with 20-25% of peel red color since they will have a high intensity of flesh browning during cold storage.